Produção de vídeos a partir das releitura dos clássicos literários como recurso de aprendizagem de língua portuguesa - Rosseti, Catarina Roberta (Universidade Federal de São Carlos, 2020)
This research aims to characterize the processes of reading and interpreting the work Auto da Barca do Inferno, by Gil Vicente for the 1st grade of the Chemistry Technician Integrated into High School of a State Technical School in the countryside of São Paulo and to problematize the didactic potentialities of audiovisual production for the development of critical reading. Our theoretical foundation is based on authors who discuss active methodologies (MORAN, 1995, 2007, 2015, 2018; VALENTE, 2018), critical reading (FREIRE, 1983, 1989, 1996) and literacy (SOARES, 1988, 2003, 2004, 2017; COSCARELLI, 2017). We proceeded to the analysis of the production process of audiovisual texts by students, elaborated during the classes of Portuguese Language and Literature in 2019 through a case study. The analysis criteria were: the description of the students (costume, makeup, satisfaction); reconstruction of dialogues (language used, quotations and intertextuality); description of the environment (location used for rehearsals, filming and scenarios); description of special situations: autonomy, interaction between teams, innovation, creativity and use of sound effects). The results of our analyzes show didactic potentialities in the production of videos for the development of critical reading in Portuguese language classes such as better understanding of the work read, vocabulary learning, as well as the ability to reflect and communicate, autonomy, resilience, critical thinking and aptitude to solve problems.
Video production from the re-reading of literary classics as a resource for learning Portuguese
Keywords: Leitura crítica; Retextualização; Audiovisual; Ensino de literatura; Auto da Barca do Inferno; Critical reading; Retextualization; Audio-visual; Literature teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO